Axl, Ferritin, Insulin‐Like Growth Factor Binding Protein 2, and Tumor Necrosis Factor Receptor Type II as Biomarkers in Systemic Lupus Erythematosus. Issue 9 (28th July 2016) - Mok, Chi Chiu; Ding, Hui Hua; Kharboutli, Marwa; Mohan, Chandra
Abstract : Objective: To evaluate the performance of 4 serum protein markers for detecting concurrent clinical activity in patients with systemic lupus erythematosus (SLE). Methods: Consecutive patients who fulfilled ≥4 American College of Rheumatology classification criteria for SLE and healthy controls were recruited for serologic testing of 4 protein markers identified by antibody‐coated microarray screen, namely Axl, ferritin, insulin‐like growth factor binding protein 2 (IGFBP‐2), and tumor necrosis factor receptor type II (TNFRII). SLE disease activity was assessed by the Safety of Estrogens in Lupus Erythematosus National Assessment version of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and physician's global assessment (PGA). Levels of these markers were correlated with SLEDAI scores, and their sensitivity and specificity for clinical SLE activity were determined. Results: A total of 94 SLE patients (98% women, mean ± SD age 28.7 ± 9.4 years, mean ± SD disease duration 5.4 ± 5.0 years) and 49 healthy controls were studied. Fifty‐two patients had clinically active SLE (defined as SLEDAI score ≥6 or having a flare). The serum concentrations of Axl, ferritin, IGFBP‐2, and TNFRII were significantly higher in patients with active SLE than in those with inactive SLE or in controls. The levels of these markers correlated strongly and significantly with anti–double stranded DNA (anti‐dsDNA), C3, and clinical SLEDAI and PGA scores. These markers were more specific, but less sensitive, in detecting concurrent SLE activity than elevated anti‐dsDNA or depressed C3. Levels of Axl, TNFRII, and IGFBP‐2, but not ferritin, could differentiate active renal from active nonrenal or inactive SLE. The specificity of Axl and IGFBP‐2 for concurrent active lupus nephritis was higher than anti‐dsDNA or C3. Conclusion: Serum proteomic markers are potentially useful for diagnosing SLE and monitoring disease activity. The performance of Axl and IGFBP‐2 in lupus nephritis should be further explored in a longitudinal cohort of SLE patients.